Success of restoration strategies in preventing extirpation of 2 critically endangered coral species - Erinn M. Muller; Mark C. Ladd; Richard Karp; Phanor H. Montoya‐Maya; Ilsa B. Kuffner; Andrew C. Baker; Erich Bartels; Amanda Bourque; Abigail S. Clark; Nikkie Cox; Martine D'Alessandro; Ben Daughtry; et al. (Conservation Biology, 2026)
An unprecedented marine heatwave in 2023 caused widespread coral bleaching and mortality throughout the Caribbean. In the Florida Keys (USA), 2 foundation species, elkhorn coral ( Acropora palmata ) and staghorn coral ( Acropora cervicornis ), were severely affected. These species have been the primary focus of reef restoration in Florida for decades. Substantial losses of these species occurred in outplanted populations, in ocean‐based nurseries, and among remnant wild colonies, leading to uncertainty over their future in the Florida Keys, given recent observed trends in climate conditions. However, the past 2 decades of restoration activity created a community of experts, a network of ocean‐based and land‐based coral‐rearing infrastructure, and 2 independent land‐based coral gene banks that prevented regional extirpation and preserved much of the genetic richness of these critically endangered coral species. Without the past decades of effort and the emergency response associated with the 2023 bleaching event, Florida acroporids would largely have been lost. This outcome afforded by the restoration network in Florida demonstrates the value of proactively establishing resources prior to major disturbances. We identified several critical strategies that, in the context of existing climate change, are preventing the extirpation of coral species in Florida, including extending collaborative restoration efforts to solidify a network of trained experts; establishing trust‐focused relationships among management agencies and restoration groups; testing direct interventions to reduce light and temperature stress early during thermal anomalies; developing redundant ocean‐based and land‐based nurseries; and establishing living coral gene banks prior to major threats to prevent the extirpation of coral species.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Status of Florida’s pillar coral population: in situ declines and ex situ successes - Karen L. Neely; Rachel M. Morgan; Keri L. O’Neil; Nikkie Cox; David S. Gilliam; Michelle B. Mair; Brian K. Walker; Amanda Zummo; Cailin Harrell; Ananda Ellis (Frontiers in Marine Science, 2025)
The population of pillar coral, Dendrogyra cylindrus , in Florida was decimated from 2013 to 2020, primarily by the emergence of stony coral tissue loss disease (SCTLD). Monitoring of survivors from 2021 to early 2025 showed that the population underwent an additional 96% decline in live tissue, a 78% loss in living colonies, and a 55% loss of genotypes. SCTLD continued to be the primary cause of these losses. Although some surviving tissue isolates exhibited small amounts of growth, the population remains extremely small, with only an estimated 9.6 m 2 of tissue remaining on 23 colonies (15 genotypes). Additionally, the colonies are far too dispersed to successfully fertilize spawned gametes. Further declines in the population since 2020 highlight the instability of the remnant population and underscore the value of the pillar coral rescue program and ongoing propagation efforts. As of February 2025, eight different in situ and ex situ facilities were caring for rescued D. cylindrus . Experimental fragmentation at one in situ nursery identified variable, but continually improving, growth rates across multiple fragmentation events. Sexual propagation efforts at an ex situ nursery documented 105 different rescue fragments spawning over 5 years. The smallest fragment was 9 cm × 7 cm × 9 cm, suggesting a potential “minimum colony size” for this species to have reproductive capacity. During these spawning events, 82 juveniles were being raised ex situ in early 2025. Two of these sexually propagated juveniles spawned 6 years after settlement, thus establishing a potential minimum age for reproduction.

Root aphid (Aploneura lentisci) population size on perennial ryegrass is determined by drought and endophyte strain - Katrin G. Hewitt; Rainer W. Hofmann; Oliver J. Ball; Neil Cox; Racheal H. Bryant; Sarah C. Finch; Alison J. Popay (Journal of Pest Science, 2024)
Climate change is anticipated to lead to an increase in the occurrence and intensity of drought and fluctuations in insect cycles that will challenge modern pasture systems. Feeding by root aphids such as Aploneura lentisci Pass. can be a significant challenge to pastures. These below-ground living aphids are commonly found in New Zealand and Australia, feeding year-round on the roots of graminaceous plants such as perennial ryegrass ( Lolium perenne L.). Some strains of the fungal endophyte Epichloë festucae var. lolii in perennial ryegrass can provide protection against root aphids and greater resilience under drought, contributing to higher persistency and growth than endophyte-free plants. However, the interaction between insect pressure and drought is not understood. This study examined the effect of drought on root aphid populations and plant performance in perennial ryegrass plants relative to endophyte status (±) and endophyte strain (AR37, NZ CT ) in a glasshouse experiment. Plants were cloned across the drought and well-watered treatments, and half of the plants were inoculated with root aphids, whilst half of the plants were treated with insecticide. Endophyte infection with strain NZ CT and AR37 reduced root aphid numbers. Aphid populations were significantly higher in drought-stressed than in well-watered plants in both endophyte-infected and endophyte-free treatments. Under drought conditions, root aphid populations were increased 4-fold in NZ CT and 8-fold in AR37 and endophyte-free plants in comparison with their well-watered counterparts. Root aphids reduced shoot dry weight by 16% in drought-exposed and 26% in well-watered plants in comparison with their insecticide-treated counterparts whilst reducing root biomass by 49%. Our results suggest that root aphids are likely able to exploit the higher availability of amino acids in the plant sap of drought-exposed plants. This study provides evidence that climate change-mediated impacts of root aphids could reduce production in perennial ryegrass-dominant pastures. However, field trials would be necessary to determine whether this effect is seen in situ, where numerous additional factors will be operating at the same time.

European marine omics biodiversity observation network: a strategic outline for the implementation of omics approaches in ocean observation - Ioulia Santi; Odette Beluche; Mélanie Beraud; Pier Luigi Buttigieg; Raffaella Casotti; Cymon J. Cox; Michael Cunliffe; Neil Davies; Oihane Diaz de Cerio; Katrina Exter; Anne Emmanuelle Kervella; Georgios Kotoulas; et al. (Frontiers in Marine Science, 2023)
Marine ecosystems, ranging from coastal seas and wetlands to the open ocean, accommodate a wealth of biological diversity from small microorganisms to large mammals. This biodiversity and its associated ecosystem function occurs across complex spatial and temporal scales and is not yet fully understood. Given the wide range of external pressures on the marine environment, this knowledge is crucial for enabling effective conservation measures and defining the limits of sustainable use. The development and application of omics-based approaches to biodiversity research has helped overcome hurdles, such as allowing the previously hidden community of microbial life to be identified, thereby enabling a holistic view of an entire ecosystem’s biodiversity and functioning. The potential of omics-based approaches for marine ecosystems observation is enormous and their added value to ecosystem monitoring, management, and conservation is widely acknowledged. Despite these encouraging prospects, most omics-based studies are short-termed and typically cover only small spatial scales which therefore fail to include the full spatio-temporal complexity and dynamics of the system. To date, few attempts have been made to establish standardised, coordinated, broad scaled, and long-term omics observation networks. Here we outline the creation of an omics-based marine observation network at the European scale, the European Marine Omics Biodiversity Observation Network (EMO BON). We illustrate how linking multiple existing individual observation efforts increases the observational power in large-scale assessments of status and change in biodiversity in the oceans. Such large-scale observation efforts have the added value of cross-border cooperation, are characterised by shared costs through economies of scale, and produce structured, comparable data. The key components required to compile reference environmental datasets and how these should be linked are major challenges that we address.

Maternal Undernutrition Induces Cell Signalling and Metabolic Dysfunction in Undifferentiated Mouse Embryonic Stem Cells - Pooja Khurana; Andrew Cox; Barira Islam; Judith J. Eckert; Sandrine Willaime-Morawek; Joanna M. Gould; Neil R. Smyth; Patrick C. McHugh; Tom P. Fleming (Stem Cell Reviews and Reports, 2023)
Peri-conceptional environment can induce permanent changes in embryo phenotype which alter development and associate with later disease susceptibility. Thus, mouse maternal low protein diet (LPD) fed exclusively during preimplantation is sufficient to lead to cardiovascular, metabolic and neurological dysfunction in adult offspring. Embryonic stem cell (ESC) lines were generated from LPD and control NPD C57BL/6 blastocysts and characterised by transcriptomics, metabolomics, bioinformatics and molecular/cellular studies to assess early potential mechanisms in dietary environmental programming. Previously, we showed these lines retain cellular and epigenetic characteristics of LPD and NPD embryos after several passages. Here, three main changes were identified in LPD ESC lines. First, their derivation capacity was reduced but pluripotency marker expression was similar to controls. Second, LPD lines had impaired Mitogen-activated protein kinase (MAPK) pathway with altered gene expression of several regulators (e.g., Maff , Rassf1 , JunD ), reduced ERK1/2 signalling capacity and poorer cell survival characteristics which may contribute to reduced derivation. Third, LPD lines had impaired glucose metabolism comprising reduced upstream enzyme expression (e.g., Gpi, Mpi ) and accumulation of metabolites (e.g., glucose-6-P, fructose-6-P) above the phosphofructokinase (PFK) gateway with PFK enzyme activity reduced. ESC lines may therefore permit investigation of peri-conceptional programming mechanisms with reduced need for animal experimentation. Graphical Abstract

Done but not dusted: Reflections on the first global reptile assessment and priorities for the second - Shai Meiri; David G. Chapple; Krystal A. Tolley; Nicola Mitchell; Timrat Laniado; Neil Cox; Phil Bowles; Bruce E. Young; Gabriel Caetano; Julia Geschke; Monika Böhm; Uri Roll (Biological Conservation, 2023)

Coastal seascape variability in the intensifying East Australian Current Southern Extension - Lachlan R. Phillips; Neil Malan; Moninya Roughan; Robert Harcourt; Ian Jonsen; Martin Cox; Andrew S. Brierley; David Slip; Adam Wilkins; Gemma Carroll (Frontiers in Marine Science, 2022)
Coastal pelagic ecosystems are highly variable in space and time, with environmental conditions and the distribution of biomass being driven by complex processes operating at multiple scales. The emergent properties of these processes and their interactive effects result in complex and dynamic environmental mosaics referred to as “seascapes”. Mechanisms that link large-scale oceanographic processes and ecological variability in coastal environments remain poorly understood, despite their importance for predicting how ecosystems will respond to climate change. Here we assessed seascape variability along the path of the rapidly intensifying East Australian Current (EAC) Southern Extension in southeast Australia, a hotspot of ocean warming and ecosystem tropicalisation. Using satellite and in situ measures of temperature, salinity and current velocity coupled with contemporaneous measurements of pelagic biomass distribution from nine boat-based active acoustic surveys in five consecutive years, we investigated relationships between the physical environment and the distribution of pelagic biomass (zooplankton and fish) at multiple timescales. Survey periods were characterised by high variability in oceanographic conditions, with variation in coastal conditions influenced by meso-to-large scale processes occurring offshore, including the position and strength of eddies. Intra-annual variability was often of a similar or greater magnitude to inter-annual variability, suggesting highly dynamic conditions with important variation occurring at scales of days to weeks. Two seascape categories were identified being characterised by (A) warmer, less saline water and (B) cooler, more saline water, with the former indicating greater influence of the EAC on coastal processes. Warmer waters were also associated with fewer, deeper and less dense biological aggregations. As the EAC continues to warm and penetrate further south, it is likely that this will have substantial effects on biological activity in coastal pelagic ecosystems, including a potential reduction in the accessibility of prey aggregations to surface-feeding predators and to fisheries. These results highlight the import role of offshore oceanographic processes in driving coastal seascape variability and biological activity in a region undergoing rapid oceanic warming and ecological change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Cross-reactivity of Haemophilus influenzae type a and b polysaccharides: molecular modeling and conjugate immunogenicity studies - Nicole I. Richardson; Michelle M. Kuttel; Frank St. Michael; Chantelle Cairns; Andrew D. Cox; Neil Ravenscroft (Glycoconjugate Journal, 2021)

Why are pandas so obsessed with horse manure? - Li Zhang; Biao Yang; Neil Cox (Science China Life Sciences, 2021)

Characterisation of the effect of day length, and associated differences in dietary intake, on the gut microbiota of Soay sheep - Nadine A. Thomas; Andrea M. Olvera-Ramírez; Leticia Abecia; Clare L. Adam; Joan E. Edwards; Georgina F. Cox; Patricia A. Findlay; Elodie Destables; Tracy A. Wood; Neil R. McEwan (Archives of Microbiology, 2019)

Collaborative research partnerships inform monitoring and management of aquatic ecosystems by Indigenous rangers - Rebecca J. Dobbs; Christy L. Davies; Michelle L. Walker; Neil E. Pettit; Bradley J. Pusey; Paul G. Close; Yoshi Akune; Ninjana Walsham; Brendan Smith; Albert Wiggan; Preston Cox; Douglas P. Ward; et al. (Reviews in Fish Biology and Fisheries, 2016)

Natural hazards in Australia: sea level and coastal extremes - Kathleen L. McInnes; Christopher J. White; Ivan D. Haigh; Mark A. Hemer; Ron K. Hoeke; Neil J. Holbrook; Anthony S. Kiem; Eric C. J. Oliver; Roshanka Ranasinghe; Kevin J. E. Walsh; Seth Westra; Ron Cox (Climatic Change, 2016)

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Reinvasion by ship rats (Rattus rattus) of forest fragments after eradication - Carolyn M. King; John G. Innes; Dianne Gleeson; Neil Fitzgerald; Tom Winstanley; Barry O’Brien; Lucy Bridgman; Neil Cox (Biological Invasions, 2011)

Uncertainty of global warming potential for milk production on a New Zealand farm and implications for decision making - Claudine Basset-Mens; Francis M. Kelliher; Stewart Ledgard; Neil Cox (The International Journal of Life Cycle Assessment, 2009)

A Standard Lexicon for Biodiversity Conservation: Unified Classifications of Threats and Actions - NICK SALAFSKY; DANIEL SALZER; ALISON J. STATTERSFIELD; CRAIG HILTON‐TAYLOR; RACHEL NEUGARTEN; STUART H. M. BUTCHART; BEN COLLEN; NEIL COX; LAWRENCE L. MASTER; SHEILA O'CONNOR; DAVID WILKIE (Conservation Biology, 2008)
An essential foundation of any science is a standard lexicon. Any given conservation project can be described in terms of the biodiversity targets, direct threats, contributing factors at the project site, and the conservation actions that the project team is employing to change the situation. These common elements can be linked in a causal chain, which represents a theory of change about how the conservation actions are intended to bring about desired project outcomes. If project teams want to describe and share their work and learn from one another, they need a standard and precise lexicon to specifically describe each node along this chain. To date, there have been several independent efforts to develop standard classifications for the direct threats that affect biodiversity and the conservation actions required to counteract these threats. Recognizing that it is far more effective to have only one accepted global scheme, we merged these separate efforts into unified classifications of threats and actions, which we present here. Each classification is a hierarchical listing of terms and associated definitions. The classifications are comprehensive and exclusive at the upper levels of the hierarchy, expandable at the lower levels, and simple, consistent, and scalable at all levels. We tested these classifications by applying them post hoc to 1191 threatened bird species and 737 conservation projects. Almost all threats and actions could be assigned to the new classification systems, save for some cases lacking detailed information. Furthermore, the new classification systems provided an improved way of analyzing and comparing information across projects when compared with earlier systems. We believe that widespread adoption of these classifications will help practitioners more systematically identify threats and appropriate actions, managers to more efficiently set priorities and allocate resources, and most important, facilitate cross‐project learning and the development of a systematic science of conservation.

Species Review of Amphibian Extinction Risks in Madagascar: Conclusions from the Global Amphibian Assessment - FRANCO ANDREONE; JOHN E. CADLE; NEIL COX; FRANK GLAW; RONALD A. NUSSBAUM; CHRISTOPHER J. RAXWORTHY; SIMON N. STUART; DENIS VALLAN; MIGUEL VENCES (Conservation Biology, 2005)
We assessed the extinction risks of Malagasy amphibians by evaluating their distribution, occurrence in protected areas, population trends, habitat quality, and prevalence in commercial trade. We estimated and mapped the distribution of each of the 220 described Malagasy species and applied, for the first time, the IUCN Red List categories and criteria to all species described at the time of the assessment. Nine species were categorized as critically endangered, 21 as endangered, and 25 as vulnerable. The most threatened species occur on the High Plateau and/or have been subjected to overcollection for the pet trade, but restricted extent of occurrence and ongoing habitat destruction were identified as the most important factors influencing extinction threats. The two areas with the majority of threatened species were the northern Tsaratanana‐Marojejy‐Masoala highlands and the southeastern Anosy Mountains. The current system of protected areas includes 82% of the threatened amphibian species. Of the critically endangered species, 6 did not occur in any protected area. For conservation of these species we recommend the creation of a reserve for the species of the Mantella aurantiaca group, the inclusion of two Scaphiophryne species in the Convention on the International Trade in Endangered Species Appendix II, and the suspension of commercial collecting for Mantella cowani. Field surveys during the last 15 years reveal no pervasive extinction of Malagasy amphibians resulting from disease or other agents, as has been reported in some other areas of the world.

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)